Air Pollution, Climate Change, and Human Health in Indian Cities: A Brief Review - Kaur, Rajveer; Pandey, Puneeta (Frontiers in Sustainable Cities, 2021)
Climate change and air pollution have been a matter of serious concern all over the world in the last few decades. The urban clusters have significant impact on both climate change and air pollution levels in the atmosphere. The human activities such as changing land use land cover, emissions of harmful gases to the atmosphere from fossil fuel and stubble burning, forest fires, power plants, automobiles and industries and roadside dust particles significantly contribute to air pollution; thereby depleting air quality. The air pollutants (such as aerosols) affect the climate of Earth both directly (by absorption and scattering) and indirectly (by altering the cloud properties and radiation transfer processes). The influence of these air pollutants further extends to impact on biogeochemical cycles, hydrological processes, human health and land surface processes. Monitoring of air quality becomes imperative in present times due to elevated air pollution levels. Poor air quality is linked with higher air-borne diseases that can be hazardous to human health. Air pollutants that are inhaled by humans and enter the respiratory system have potential to cause serious health impacts such as respiratory complications, carcinogenesis, cardiovascular diseases and even premature death. Also, higher exposure to air pollutants such as the Particulate Matter 2.5 is linked with higher morbidity and mortality rates due to cardiovascular and respiratory diseases. Further, the intensified heat waves as a result of climate change lead to the elevation in temperature levels causing thermal discomfort and several health issues to urban residents. Hence, an attempt is being made in the present study to critically evaluate the role of air pollutants in climate change for urban areas. Further, the role of air pollutants and particulate matter (aerosols) also needs to be examined in detail. Thus, the present study explores the status of air pollution in selected Indian cities and its effect on human health in these cities. This will serve as a baseline data for policy makers in analyzing vulnerable regions and implementing mitigation plans for tackling air pollution.